Advanced Study on Resource-Saving Methods of Forming Information Infrastructure of Sorting Stations - Anatolii Kosolapov (New Ideas Concerning Science and Technology Vol. 4, 2021)
This chapter discusses a resource-saving method for choosing a rational structure of an automated control system when technical structure migration from a centralized system based on a powerful processor to a functionally distributed system based on microcontrollers. The method allows you to determine a rational number of subsystems that effectively use the computing and financial resources of the project. The approach is illustrated by a real example of designing an automated control system for a marshalling yard.